VIABILIDADE DO EMPREGO DE CANA-DE-AÇÚCAR PARA A REGIÃO SUL DO BRASIL: SITUAÇÃO ATUAL, LIMITAÇÕES E PERSPECTIVAS - Melo, Elder D.; Krüger, Cleusa A. M. B.; Quadros, Valmir J. d.; Silva, Adair J. d.; Cadore, Pablo R.; Dambrós, Rodrigo; Soares, Rômulo D.; Vezzosi, Leandro F.; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo